Optimalisasi Pelatihan Karyawan di Kartika Bawen untuk Meningkatkan Kualitas SDM dan Daya Saing di Industri Garmen - Julian Trisnawati Bali; Syamsul Hadi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This study aims to analyze the impact of the employee training program implemented by the Kartika Bawen Training Institution in enhancing human resource (HR) quality and competitiveness in the garment industry. The garment industry faces intense competition, making HR quality a key factor in improving productivity and company performance. This research focuses on how appropriate training can improve employee competencies, skills, and motivation. To achieve this goal, the approach used is based on human resource management and employee training theories. Data was collected through in-depth interviews with employees, management, and trainers, as well as direct observations of the ongoing training process. The findings show that well-designed training programs significantly contribute to the improvement of employees' technical skills and soft skills, which positively impact work productivity by 20%. In addition, the training also boosts employees' confidence and prepares them to face challenges in a dynamic work environment. These findings emphasize the importance of structured and continuous training strategies in creating competitive advantages and driving performance improvements in the garment industry.